When global problems come home: Engagement with climate change within the intersecting affective spaces of parenting and activism. (August 2022) - Howard, Lisa
Abstract: Emotional engagement with climate change has been identified as an important research agenda. Recent studies have suggested parental worry for children and future generations are motives for climate activism, highlighting both personal and social justice concerns. A global parent-led climate justice movement specifically articulating this has emerged, yet currently remains under-researched. At the same time, social movement research has tended to overlook the social embeddedness of activism. To address these gaps in knowledge, this study used a qualitative mix of diary entries and interviews of UK-based mothers and fathers to investigate the overlapping emotional spaces of climate activism and parenting. It found that a parental lens on climate, informed by dystopian imaginings and processes of responsibilisation amplified fear and risk-related feelings, but were managed by channelling energy into a diverse array of collective action spaces. This led to positive emotions of hope and solidarity which were fostered and circulated within close personal relationships. In addition, the study found times and spaces which put a strain on affective engagement, and on partner relationships. The paper discusses the lack of moral anger in this sample of climate activists compared to previous research, and calls for further enquiry into the movement's development of intergenerational justice grievances. Highlights: Examines the circulation of emotions within intergenerational climate justice activism, parenting and family life. Parents make sense of, and foster, emotions of fear, hope and solidarity within particular affective spaces. Spousal relationships and parenting demands can be unsupportive of climate-related emotions. Righteous anger is suppressed, having implications for wider discourses around intergenerational climate injustice.